CHARACTERISTICS OF THE SENSORY QUALITY OF PATIN FISH (Pangasius djambal) USING DIFFERENT CARBOHYDRATE SOURCES - Ayu Wulandari; Tjipto Leksono; Bustari Hasan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
AbstractCatfish (Pangasius sp.) is one of the freshwater fishery commodities that have high economic value. Catfish rapidly decays, so an alternative is needed to extend its shelf life, such as Bekasam fermented products. Bekasam is traditionally processed with the addition of salt and carbohydrates. Carbohydrates serve as an energy source for lactic acid bacteria. Bekasam was made from fish mixed with salt and carbohydrate sources, then fermented 5, 7 and 9 days. The treatments were different carbohydrate sources consisting of boiled rice (N), roasted rice (B) and roasted paddy (P). The N treatment was better based on its texture (soft texture). Bekasam treatment B was better based on its appearance (attractive yellow appearance). Bekasam treatment P was better based on its aroma (has a unique aroma from roasted paddy).Keywords: bekasam, carbohydrate source, fermentation, organoleptic